Validation of a Transformative Learning Model Based on Marosok Local Wisdom for Strengthening Students' Entrepreneurial Character - Felia Siska; Novidya Yulanda; Maria Magdalena Beatrice Sogen; Irwan Irwan; Darius Yonatan (Jurnal Mamangan, 2025)
The Marosok tradition is one of the local wisdoms of the Minangkabau culture that upholds the values of honesty, trust, responsibility, work ethic, and empathy. Due to globalization, the Marosok tradition is increasingly unfamiliar to school-aged generations. In fact, this tradition embodies entrepreneurial character values of Minangkabau traders. This study aims to elevate local community traditions as content in Social Studies education (IPS) while also preserving the local wisdom inherited from the Minangkabau society. The objective of this research is to develop a transformative learning model based on Marosok local wisdom and to produce a valid transformative learning model for Social Studies education. This research employs the Research and Development (R&D) method following the Borg & Gall model. Data collection techniques include questionnaires, focus group discussions (FGDs), interviews, and observations. The data analysis technique uses descriptive statistics. The research findings indicate that the development of a transformative learning model based on local wisdom results in seven syntax stages: Bapatuik, formulating essential questions, designing the project, implementing the project, assessing the results, decision-making, and constructing new meaning perspectives. Model validation was carried out in two stages: Focus Group Discussion and expert validation using questionnaires. The FGD stage recommended that the learning model could proceed to the implementation phase with a suggestion to reduce the decision-making syntax stage. The results of the model and learning tools validation by experts in model design, content, language, and practicing teachers indicated an average validity score of 93%, confirming that the transformative learning model based on Marosok local wisdom is valid for school implementation. The conclusion of this study is that the Marosok-based local wisdom learning model has been developed and is valid for use in Social Studies learning at the junior secondary level (SMP/MTs), with the potential to strengthen students’ entrepreneurial character